Juridical Study of the Meme Phenomenon in Social Media - Isnawan, Fuadi (Nagari Law Review, 2025)
This paper examines the role of forensic linguistics in identifying and analyzing memes that contain elements of defamation or insult on social media platforms. In the digital age, memes have become a prevalent form of communication, often blurring the lines between humor and harmful content. This study highlights how such memes can violate Indonesian law, specifically the Criminal Code and the Electronic Information and Transactions (ITE) Law, by spreading false information and damaging the reputations of individuals or entities. This research uses the normative legal research method. The result of this research is memes can indeed contain elements of defamation or insult, violating both the Criminal Code and the Electronic Information and Transactions (ITE) Law in Indonesia. The ITE Law, notably Article 27, paragraph (3), provides a progressive framework for addressing defamation and insult through digital media, imposing criminal penalties on those who intentionally and without rights to distribute, transmit, or make accessible defamatory or insulting content. This law is more effective in the digital age than the Criminal Code, as it acknowledges the rapid spread and broad reach of defamatory content on social media. Forensic linguists play a crucial role in these cases, interpreting whether a meme is defamatory or merely a joke. This distinction is vital as it determines legal consequences. If a meme contains defamation or insult, the perpetrator can face criminal sanctions; no liability arises if it is a harmless joke. Forensic linguists assess memes' context, intent, and impact, helping legal authorities understand the nuances of digital communication and ensuring that justice is served. Their expertise is vital in distinguishing harmful content from benign expressions, contributing to a fair judicial process, and protecting individuals and entities from undue harm while maintaining freedom of expression.